The Art of Debating by the Prophet Ibrāhīm: Analysis of Ma'nā cum maghzā's Approach to Q. 2: 258 - Muhammad Arman Al Jufri (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2022)
This article delves more deeply into the prophet Ibrāhīm's art of debating: an analysis of ma'nā maghzā's approach to Q. 2: 258. The difference of views is a fact that cannot be denied. The debates that occur often lead to the presence of further conflicts, both at the regional, national, and international levels. Two points are outlined, first, how to use Q. 2: 258 in its language and socio-historical manner; Second, what is the significance of Q. 2: 258. This article is a type of qualitative research in the form of library research. The primary data source in this study is Q. 2: 258. While secondary data sources include literature that is directly or indirectly related, both in physical and online libraries. To see it, this article uses the ma'nā cum maghzā approach offered by Sahiron Shamsuddin. As a result, in language, Q. 2: 258 is a verse that specifically speaks to a debate that took place between the Prophet Ibrāhīm and King Namruż. Q. 2: 258 hints at a system of